2016
DOI: 10.5194/isprsarchives-xli-b2-299-2016
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Genetic Algorithm for Finding Fuzzy Shortest Paths in Uncertain Networks

Abstract: ABSTRACT:In realistic network analysis, there are several uncertainties in the measurements and computation of the arcs and vertices. These uncertainties should also be considered in realizing the shortest path problem (SPP) due to the inherent fuzziness in the body of expert's knowledge. In this paper, we investigated the SPP under uncertainty to evaluate our modified genetic strategy. We improved the performance of genetic algorithm (GA) to investigate a class of shortest path problems on networks with vague… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Hamidzadeh et al, (2017) suggested a chaotic bat algorithm for the weighted support vector data description. Heidari and Delavar (2016) utilized the evolutionary and swarmbased meta-heuristic algorithms (MHAs) to handle MLP networks. The meta-trainers were deployed in order to optimize not only the connection weights but also the parameters and structure of the MLP network.…”
Section: Highlightsmentioning
confidence: 99%
“…Hamidzadeh et al, (2017) suggested a chaotic bat algorithm for the weighted support vector data description. Heidari and Delavar (2016) utilized the evolutionary and swarmbased meta-heuristic algorithms (MHAs) to handle MLP networks. The meta-trainers were deployed in order to optimize not only the connection weights but also the parameters and structure of the MLP network.…”
Section: Highlightsmentioning
confidence: 99%
“…A key significant strength of the SI algorithms is their global search capability as they can produce multiple solutions in each run. A common challenge for all metaheuristics is the parameter settings since they usually have a set of initial parameters to be tuned [33]. The process of tuning parameter has significant impacts on the performance of the searching process, but it is very timeconsuming.…”
Section: Introductionmentioning
confidence: 99%